The causes of pulmonary hypertension and the benefits of aerobic exercise for pulmonary hypertension from an integrated perspective - Song, Yinping; Jia, Hao; Ma, Qing; Zhang, Lulu; Lai, Xiangyi; Wang, Youhua (Frontiers in Physiology, 2024)
Pulmonary hypertension is a progressive disease of the pulmonary arteries that begins with increased pulmonary artery pressure, driven by progressive remodeling of the small pulmonary arteries, and ultimately leads to right heart failure and death.Vascular remodeling is the main pathological feature of pulmonary hypertension, but treatments for needle pulmonary hypertension are lacking. Determining the process of vascular proliferation and dysfunction may be a way to decipher the pathogenesis of pulmonary hypertension. In this review, we summarize the important pathways of pulmonary hypertension pathogenesis. We show how these processes are integrated and emphasize the benign role of aerobic exercise, which, as an adjunctive therapy, may be able to modify vascular remodeling in pulmonary hypertension.